A governan??a ambiental do setor hidrel??trico no Brasil: as contribui????es dos instrumentos de avalia????o de impacto - Gaudereto, Guilherme Leite (2017)
The environmental governance is a concept that can be understood as a framework for the environment. With the objective of analyze the contribution of three instruments of Impact Assessment (IA) to the environmental governance of the hydroelectric sector, this work sought to contribute to the understanding of the functioning and mechanisms of this governance. The hydroelectric sector, while is known for its significant impact on environmental due infrastructure, is a pioneer in the use of AI instruments, including the Environmental Impact Assessment (EIA), Integrated Environmental Assessment (AAI) And with some experiences of Strategic Environmental Assessment (SEA). As there is no much exploration in this theme, the objective of this work, a research of quality and exploratory nature has been carried out, which results in an analysis on the main dynamics, regulatory frameworks and institutional mapping of the hydroelectric sector. For that, an environmental governance analysis was developed on two smaller systems, the electric sector and the protection of the environment sector, which in turn, a set of structures of water resources management and application of the Environmental Policy. The results of the study indicate that the IA instruments, when used, contribute to the strengthening of the governmental environmental structure of the hydroelectric sector, especially if the SEA is adopted, following principles of international good practices. The research also indicates that the current structure of environmental governance is weak, not having a definition of environmental guidelines for the sector and lacking mechanisms for coordination, implementation, monitoring and evaluation of the goals.